Sobrevida, aspectos psicossociais, qualidade de vida e dor de pacientes com câncer de cabeça e pescoço: um estudo longitudinal. - Mahl, Claudiane (2021)
Introduction: Head and neck cancer is considered one of the most aggressive cancers, with low survival, negative impact on quality of life, and psychosocial factors of patients. Objective: To assess survival, psychosocial aspects, quality of life, and pain in patients with head and neck cancer in the state of Sergipe, Northeast Brazil. Methodology: This is a longitudinal study with patients diagnosed with head and neck cancer from August 2017 to June 2020. Quality of life, pain, anxiety, depressive symptoms, social support, spirituality, resilience, and pain catastrophizing were evaluated with validated instruments in three times: at the beginning, at the end, and one year after the end of the cancer treatment. The minimum sample size was estimated at 47 patients, based on non-parametric one-sample survival analysis. Data were examined for loss to follow-up, outliers, normality, and linearity. Survival was calculated using the Kaplan-Meier product-limit estimator, the factors associated to death by using a Cox regression analysis, the comparison of quality of life scores, psychosocial factors, and pain between survivors and non-survivors was performed by using the Mann- Whitney test, and the changes in these scores over time among survivors were analyzed by the Friedman test with posthoc Conover test. Results: Seventy-nine patients were included in this study and most of them were men, had a mean age of 55 years, low income and education, were smokers and diagnosed with lesions at an advanced stage. The overall survival at 12 and 24 months of follow-up was 50.6% and 39.4%, respectively. Male gender and not having a partner was associated with death. Worse quality of life scores, anxiety, depressive symptoms, social support, spirituality, and resilience at the beginning of the treatment was associated with mortality. Among survivors, psychological behavior, pain perception, and quality of life were stable, with few changes from the beginning to one year after the end of treatment. Patients who had delayed follow-up during the pandemic were at increased risk for self-medication. Conclusion: The results of this study showed the need to assess the quality of life and psychosocial markers before starting oncological treatment, seeking to identify a profile more susceptible to worse clinical outcomes.